Предмет:
МатематикаАвтор:
анонимНайдем значение выражений. Для этого, раскроем скобки и упростим выражение.
Получаем:
1) 5 * a + (-8 * b) + (-7 * c) + (-2 * a) + 3 * b + c = 5 * a - 8 * b - 7 * c - 2 * a + 3 * b + c = 3 * a - 6 * c - 5 * b;
2) 3 * n + 6 * m + (-15 * k) + (-n) + (-5 * m) + 8 * k = 3 * n + 6 * m - 15 * k - n - 5 * m + 8 * k = 2 * n + m - 7 * k;
3) 8,2 * a + (-4 * b) + 10,3 * c + (-4 * a) + (-9,5 * b) + (-8 * c) = 8.2 * a - 4 * b + 10.3 * c - 4 * a - 9.5 * b - 8 * c = 4.2 * a - 13.5 * b + 2.3 * c.
Автор:
zhangДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть